The problem of construction on salted soils due to insufficient use of Underground Water of the Bukhara Region - Zhumagul Rakhimberdievna Turgunbaeva; Gulchekhra Bakidzhanovna Ismailova; Muslimakhon Tokhirboevna Yakhyaeva; Gulirano Turgunboy kizi Alieva (Research Parks Publishing LLC, 2021)
The article investigates and conducts complex geographic studies, gives a classification of soils, describes their physical properties and the problems of construction on saline soils in connection with the unsustainable use of groundwater. The high level of formation of groundwater leads to salinization and waterlogging of soils on the surface layer. In this regard, it is necessary to carefully monitor soils prone to salinization and waterlogging, careful monitoring of soils is recommended, a high level of groundwater occurrence, by reducing unproductive water losses by streamlining its distribution at all levels of systems, repairing canals and cleaning the collector